BMI, pre-exercise meal timing, and running performance in college students: A mediation model - Hasan, Muhammad Fahmi; Apriantono, Tommy; Ilsya, Marisa Noviyanti Fajrah; Latief, Gifran Rihla Gifarka; Juniarsyah, Agung Dwi (UIR Press, 2026)
Background: Body Mass Index (BMI) is widely used as an indicator of body composition and nutritional status, yet its interaction with nutritional habits—particularly pre-exercise meal timing—remains underexplored among college students. Understanding these relationships is important for promoting active and healthy lifestyles within this population. Objectives: This study aims to test a mediation model in which pre-exercise meal timing serves as a potential mechanism linking BMI to running performance among college students. Methods: This quantitative study involved 213 college students who completed an online questionnaire reporting self-reported BMI, pre-exercise meal timing, and running pace (minutes per kilometre). Mediation analysis using the PROCESS macro (Model 4) in SPSS with bootstrapping procedures was applied to examine the mediating role of pre-exercise meal timing. Results: BMI was positively associated with running pace, indicating that higher BMI values were linked to slower running performance. The model explained 24.3% of the variance in running pace (R² = 0.243). The indirect effect of pre-exercise meal timing was minimal and not statistically significant (B = −0.004, 95% CI [−0.010, 0.001]), suggesting a limited mediating role. Students with higher BMI tended to consume meals closer to exercise time, reflecting potential behavioral differences. Conclusion: Although the mediating role of pre-exercise meal timing was negligible, BMI remained a significant predictor of running performance among college students. These findings suggest that physiological factors may play a more prominent role than short-term dietary timing in endurance outcomes. Campus health interventions may benefit from integrating body composition management with balanced nutritional strategies to enhance student fitness and well-being.